AB0641 Urinary CXCL-10 and MCP-1 are good markers to assess activity of lupus nephritis. (23rd January 2014) - Abujam, B.; Cheekatla, S.S.; Aggarwal, A.
Abstract : Background: Interferon-γ-inducible protein 10 (IP-10) or chemokine (C-X-C motif) ligand 10 (CXCL 10) and Monocyte chemo-attractant protein-1 (MCP- 1) are chemokines involved in immune pathogenesis of lupus nephritis and may be useful biomarkers. Objectives: To look at the utility of serum and urinary IP-10 and MCP-1 as biomarkers for lupus generalised and renal activity. Methods: SLE patients fulfilling ACR 1997 criteria (both adult and children) were recruited and blood and urine samples collected. Disease activity was assessed by SLEDAI and active lupus defined as SLEDAI ≥4. Active patients further divided into active renal and active non-renal lupus based on urinary parameters (proteinuria ≥500 mg/day or active sediment in urine). Kidney biopsy was done in some cases as per the treating physician's decision or patient consent. Patients with active renal lupus were followed until disease became inactive. Healthy controls also reruited. Serum and urinary levels of MCP-1 and IP-10 (pg/ml) were measured by ELISA. Urinary values were normalised for urinary creatinine. Data presented as median (interquartile range). Mann Whitney U test, kruskal-wallis used to compare median levels between groups. Paired t test used to compare longitudinal values. Results: Study included 136 patients with SLE including 78 active (46 active renal and 32 active non renal). Median age was 25 (10-55) years and SLE duration was 23 (6-48) months. Serum and urinary levels of MCP-1 and IP-10 were higher in active compared to inactive SLE as well as healthy controls (Table 1 ). However, in active renal compared to active non-renal SLE, only urinary but not serum levels of MCP-1 and IP-10 were higher (Table 1). Out of the 46 renal active patients, kidney biopsy done in 31: class IV 25, class III 4, class V 2. If consider only biopsy proven proliferative nephritis as "true active renal", still urinary MCP-1 and IP-10 higher compared to both inactive and active non renal patients (p=0.003, 0.023). On ROC analysis, urinary MCP-1 better as compared to urinary IP-10 for differentiating active renal from active non renal SLE [p=0.03], in addition, urinary MCP-1 better than C4 [p<0.05]. On longitudinal follow up of active renal patients (n=24) urinary levels of MCP-1 and IP-10 [p=0.005] and serum levels of IP-10 [p=0.003] decreased. Conclusions: Urinary and serum IP-10 and MCP-1 are good markers of lupus activity. Importantly, urinary levels can differentiate renal from non-renal active disease and can be used for follow up of lupus nephritis patients. Disclosure of Interest: None Declared